2015
DOI: 10.1063/1.4935045
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic rate constants for proton transfer and proton-coupled electron transfer reactions in solution: Effects of quadratic term in the vibronic coupling expansion

Abstract: Rate constant expressions for vibronically nonadiabatic proton transfer and proton-coupled electron transfer reactions are presented and analyzed. The regimes covered include electronically adiabatic and nonadiabatic reactions, as well as high-frequency and low-frequency proton donor-acceptor vibrational modes. These rate constants differ from previous rate constants derived with the cumulant expansion approach in that the logarithmic expansion of the vibronic coupling in terms of the proton donor-acceptor dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(68 citation statements)
references
References 38 publications
2
66
0
Order By: Relevance
“…We have previously shown that quite small changes in H-donor-acceptor distances can lead to significant rate differences. [6d] Using previously derived expressions [7a] , we attribute the present increases in rate at 1.034 bar to a very small active site compression, of ca. 0.02 Å, that affects the H-transfer slightly less than that for D-transfer.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…We have previously shown that quite small changes in H-donor-acceptor distances can lead to significant rate differences. [6d] Using previously derived expressions [7a] , we attribute the present increases in rate at 1.034 bar to a very small active site compression, of ca. 0.02 Å, that affects the H-transfer slightly less than that for D-transfer.…”
mentioning
confidence: 96%
“…[5] Soybean lipoxygenase-1 (SLO-1, Figure 1), a prototype for the study of enzymatic C-H activation via hydrogen-tunneling, is providing a unique window into the subtle influence of protein motions on catalysis. [6,7] In the present study, we focus on understanding the underlying interaction between two distinct classes of catalysis-linked protein motions in H-transfer reactions: local distance sampling that is dependent on substrate labeling with isotopes and global conformational landscapes that are independent of this labeling. [3,5] We systematically explore the combined impact of temperature and pressure on the full set of kinetics parameters for WT SLO-1 and a range of mutants with established kinetic properties at ambient pressure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A successful framework employing Fermi's golden rule is presented by Hammes-Schiffer and co-workers [6][7][8][9][10][11][12]22,40,41 . This rate model provides a good fit to the wild-type SLO KIE data 13 as well as predicting the KIE magnitude and temperature dependence of the mutants M1, M2, M3 (and its variants 30 ) and the double mutant 11 .…”
Section: Advanced Models Of Enzyme Catalysismentioning
confidence: 99%
“…An alternative transfer mechanism is also possible: the transferring particle may tunnel 5 through the barrier instead of hopping over it. This has been discussed in a number of enzymatic systems that catalyse hydrogen transfer and have high kinetic isotope effects (KIEs), such as soybean lipoxygenase (SLO) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%